Efficacy of home-based non-pharmacological interventions for treating depression: a systematic review and network meta-analysis of randomised controlled trials. Issue 7 (12th July 2017) - Sukhato, Kanokporn; Lotrakul, Manote; Dellow, Alan; Ittasakul, Pichai; Thakkinstian, Ammarin; Anothaisintawee, Thunyarat
Abstract : Objectives: To systematically review and compare the efficacy of all available home-based non-pharmacological treatments of depression. Design: Systematic review and network meta-analysis of randomised controlled trials. Data sources: Medline, Scopus and Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases were searched since inceptions to 7 August 2016. Eligibility criteria: Randomised controlled trials comparing the efficacy of home-based non-pharmacological interventions with usual care of patients with depression were included in the review. Main outcomes: Depression symptom scores and disease remission rates at the end of treatment. Results: Seventeen studies were included in the review. Home-based non-pharmacological interventions were categorised as (1) home-based psychological intervention, (2) home-based exercise intervention, (3) combined home-based psychological intervention with exercise intervention and (4) complementary medicine. Complementary medicine approaches were excluded from the meta-analysis due to heterogeneity. The standardised mean differences of post-treatment depression symptom scores between usual care groups and home-based psychological intervention, home-based exercise intervention and combined home-based psychological intervention with exercise intervention were âˆ'0.57 (95% CI âˆ'0.84 to âˆ'0.31), âˆ'1.03 (95% CI âˆ'2.89 to 0.82) and âˆ'0.78 (95% CI âˆ'1.09 to âˆ'0.47), respectively. These results suggest that only home-based psychological intervention and combined home-based psychological intervention with exercise intervention could significantly decrease depression scores. Compared with usual care groups, the disease remission rate was also significantly higher for home-based psychological intervention (pooled risk ratio=1.53; 95%â€‰CI 1.19 to 1.98) and combined home-based psychological intervention with exercise intervention (pooled risk ratio=3.47; 95%â€‰CI 2.11 to 5.70). Of all the studied interventions, combined home-based psychological intervention with exercise intervention had the highest probability of resulting in disease remission. Conclusion: Our study confirms the efficacy of home-based psychological intervention and combined home-based psychological intervention with exercise intervention in the treatment of depression. Combined home-based psychological intervention and exercise intervention was the best treatment and should be considered for inclusion in clinical guidelines for managing depression.